PENGARUH PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Robbi Mai Prizal; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of giving organic liquid fertilizer as well as obtaining the appropriate concentration of organic liquid fertilizer in increasing the growth and production of pakcoy plants (Brassica rapa L. The experiment was conducted at Experimental Garden of Agriculture Faculty of Universitas Riau Jalan Bina Widya Km 12,5 Simpang Baru Tampan, Pekanbaru from April to June 2017. The experiment was conducted experimentally using Completely Randomized Design (RAL) consisting of 5 treatments and 4 replications. The treatment given is liquid organic fertilizer (P) consisting of 5 levels, namely: The P0 = Without the application of liquid organic fertilizer (0 cc / l water), P1 = Giving organic liquid fertilizer 2 cc / l water, P2 = Organic fertilizer Liquid 4 cc / l water, P3 = Provision of liquid organic fertilizer 6 cc / l water and P4 = Provision of liquid organic fertilizer 8 cc / l water. Thus obtained 20 units of experiments consisting of 5 tamanan as a sample. The parameters observed were: plant height, leaf number, leaf area, fresh weight of plant and fresh weight of consumption. The data obtained were analyzed using variance then tested further with the Duncan Multiple Range Test at 5% level. The results showed that the application of liquid organic fertilizer significantly affect the parameters of plant height, leaf number, leaf area, fresh weight of pakcoy plant and fresh weight is feasible for consumption. Giving of liquid organic fertilizer 8 cc / L water showed better growth and yield on all parameters of pakcoy plant. Keywords: Pakcoy, organic POC, Growth and production